Improving the approach to assessing the impact of financial market digitalization on the rationality of financial decisions - Kucher, Anatolii; Moskvyak, Yaroslava; Fedorchak, Oleksii (Technology audit and production reserves, 2025)
The object of research is the process of assessing the impact of digital transformations on the rationality of financial decisions (RFD) in the context of the functioning of modern financial markets. The problem being solved is to specify a scientifically sound approach to the integrated analysis of quantitative, qualitative and simulation characteristics, which allow for accurate determination of the effectiveness of digital technologies in the processes of financial decision-making, taking into account uncertainty, data limitations, behavioral factors and the level of digital literacy. It is proven that the growth of spending on digital technologies is closely correlated with the growth of the RDF level, which is confirmed by the results of multi-criteria analysis, ARIMA forecasting, Monte Carlo modeling and clustering. The effectiveness of the use of hybrid simulation models that combine system dynamics with an agent approach is determined, and indicators of digital sustainability of companies are also proposed. The recommendations developed to improve the approach to assessing the impact of digitalization of financial markets on RDF can be used by financial institutions, regulatory authorities and the corporate sector to assess the effectiveness of digitalization, increase the validity of financial strategies, reduce the level of risk, adapt to martial law conditions and strengthen competitiveness in the digital environment.